Circuit training on oxidative stress and arterial health: a health promotion perspective for obese adult men - Woo-Hyeon Son; Woo-Hyeon Son; Yi-Sub Kwak; Min-Seong Ha (Frontiers in Public Health)
BackgroundObesity leads to increased oxidative stress, disruption of the antioxidant system, and decreased bioavailability of nitric oxide (NO). This, in turn, contributes to impaired endothelial function. The resulting increase in arterial stiffness (AS) has been associated with an increased risk of cardiovascular disease (CVD). Regular physical activity improves the antioxidant system and vascular function. Circuit training combines aerobic exercise and resistance training, encapsulating the benefits of both types of exercise, and helps improve vascular function. We aimed to investigate the effects of circuit training on total oxidant status (TOS), total antioxidant status (TAS), NO, and atherosclerosis in adult men with obesity.MethodsA total of 25 obese men were randomly assigned to control (n = 12) or exercise groups (n = 13). The exercise group participated in circuit training three times per week for 12 weeks at an intensity corresponding to 60–80% of heart rate reserve (HRR). Anthropometrics, TOS, TAS, oxidative stress index (OSI), NO, and brachial-ankle pulse wave velocity (baPWV) were measured before and after the 12-week intervention.ResultsBody mass index (BMI) (p < 0.001), TAS (p < 0.001), OSI (p < 0.05), NO (p < 0.05), and baPWV (L, R) (p < 0.05) values improved significantly in the exercise group following the 12-week intervention, while TOS values did not demonstrate a significant change. Furthermore, no change was observed in the control group.ConclusionOur findings reveal that circuit training leads to improvements in BMI, TAS, OSI, NO, and baPWV in men with obesity, suggesting that it may contribute to an improvement in the antioxidant system and the prevention of CVD in obese men.